The Role of Otoscopy in the Diagnosis of Rare Diseases in Pediatrics. Congenital Middle Ear Cholesteatoma in the Child: Clinical Case - Irina V. Zelenkova; Svetlana G. Gubanova; Irina V. Naumova; Viktor A. Gankovskii; Madina T. Fatakhova; Leyla S. Namazova-Baranova (Педиатрическая фармакология, 2021)
The clinical recommendations “Acute respiratory viral infection (ARVI) in children" indicate that otoscopy should be a part of routine pediatric examination of each patient along with auscultation, percussion, etc. Nowadays, there are no legal regulations on which specialists can perform otoscopy. Thus, there is significant pediatricians’ interest in otoscopy, especially in diagnosis of acute otitis media (AOM) during primary examination for timely antibacterial management. Moreover, pediatricians could reveal such rare and very aggressive middle ear disease as cholesteatoma, its early diagnosis can prevent the development of any complications and determines the range and quality of rehabilitation actions.